Money Laundering and Forensic Accounting Skills in Nigerian Banks - CHRISTOPHER, EBERE (2016)
The study examines money laundering and forensic accounting skills in Nigeria banks with the purpose of finding if the extent placement, layering and integration money laundering methods are affected by forensic accounting skills. The instrument used to gather data was money laundering crime and forensic accounting skills questionnaire (MLCA-FASO) of 120 respondents. Frequency counts and descriptive statistics were used to answer the research questions and correlation was used for all the hypotheses with the aid of special package for social sciences package (SPSS). The findings reveal that those who are involved in forensic accounting practice posses good accounting qualification, sufficient skills in forensic accounting, and all the dimension of money laundering methods correlated significantly with accounting skills. Based on the findings it is therefore recommended among other things that banks should set up policies that ensure that they recruit forensic accountants to manage accounting sections. Key words: Money laundering; placement method, layering method, integration method, forensic accounting skills